Evolution of latin american approaches to integrated coastal management (ICM): paths, outcomes, and governance baselines - Perez Bolde, Carlos Francisco Castellanos (2011)
Dissertação mest., Gestão da Água e da Costa, Universidade do Algarve, 2010